OPTIMIZATION OF METHODS OF QUANTITATIVE DETERMINING FLAVANOIDS IN KNOTWEED RAW MATERIAL - Takibayeva A.T.; Kulakov I.V.; Kapbassova A.S.; Sydykova D.M.; Rakhimberlinova Zh.B. (Academic Scientific Journal of Chemistry, 2019)
The method of quantitative determination of flavonoids in the grass of the mountaineer avian is developed. Improvement of the existing Pharmacopoeia technique for determining the total content of flavonoids in the grass of the mountain bird is an urgent task, since the long procedure of extraction of raw materials of the bird mountain and the maximum extract of flavonoids. The optimal conditions of the experiment were chosen. Parameter optimization of pharmacopoeial methods is the reduction of time of the extraction of flavonoids (total extraction time 1.5 hours) with the introduction of the calculation formula of the correction factor for the incomplete extraction. The content of flavonoids in the grass of the bird Highlander determined by Pharmacopoeia was 1.62 ± 0.02%. The content of the amount of flavonoids is normalized in the raw material at a level of not less than 0.5%. To determine the metrological characteristics of the developed technique, 10 parallel definitions were carried out The relative error of definition does not exceed 3,13 %.A rapid method for determination of flavonoids in poultry sold in buckets for 5 minutes in a variant of the extraction with 70% ethanol. The definition error does not exceed 3.13 %.